Pomocy potrzebuje na teraz
4x – 3 = 3x + 5
5x + 2 = 7 – 3x
3 (x – 1) = 0
-6 (x + 1) = 24
-7 (x - 2) = 3x – 1
4 (x – 1) = 6 (1 + x)


Odpowiedź :

Szczegółowe wyjaśnienie:

4x-3=3x+5

4x-3x=5+3

1x=8

x=8:1

x=8

5x+2=7-3x

5x+3x=7-2

8x=5

x= 5:8

x=0,625

3(x-1)=0

3x=0+3

3x=3

x=3:3

x=1

-6( x+1)=24

-6x-6=24

-6x=24+6

-6x=30

x=30:(-6)

x=-5

tego nie jestem pewna

-7(x-2)=6(1+x)

-7x+14=6+6x

-7x-6x=6-14

-13x=-8

x=-8:(-13)

x=0,6

4(x-1)=6(1+x)

4x-4=6+6x

4x-6x=6+4

-2x=10

x=10:(-2)

x=-5